2023
DOI: 10.1186/s12916-022-02684-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a deep-learning-based retinal biomarker (Reti-CVD) in the prediction of cardiovascular disease: data from UK Biobank

Abstract: Background Currently in the United Kingdom, cardiovascular disease (CVD) risk assessment is based on the QRISK3 score, in which 10% 10-year CVD risk indicates clinical intervention. However, this benchmark has limited efficacy in clinical practice and the need for a more simple, non-invasive risk stratification tool is necessary. Retinal photography is becoming increasingly acceptable as a non-invasive imaging tool for CVD. Previously, we developed a novel CVD risk stratification system based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Adding Reti-CAC to the PCE enhances cardiovascular risk stratification, evidenced by a continuous net reclassification index of 0.261. Reti-CAC score Severance Main Hospital, Seoul, South Korea CMERC­HI (South Korea) SEED (Singapore) UK Biobank (UK) 527 (CMERC-HI) 33 (6.3%) of 527 had CVD events during the 5-year follow-up 8,551 (SEED) 310 (3.6%) of 8551 had CVD events 47,679 (UK Biobank) 337 (0.7%) of 47679 had CVD events Age Gender Hypertension Dyslipidaemia Diabetes Smoking status BMI Fasting glucose level Retrospective cohort study Tseng et al [ 17 ] May 2021 Reti-CVD, derived from retinal photographs, indicates a higher CVD risk, and serves as an effective tool for identifying individuals with a ≥ 10% 10-year CVD risk, including those in the borderline-QRISK3 category. It accurately identifies high-risk individuals, with a 10-year risk of 13.1% (CI: 11.7%–14.6%), enhancing early intervention and refining risk assessments, especially for those with a 10-year risk of 7.5%–10%.…”
Section: Main Textmentioning
confidence: 99%
“…Adding Reti-CAC to the PCE enhances cardiovascular risk stratification, evidenced by a continuous net reclassification index of 0.261. Reti-CAC score Severance Main Hospital, Seoul, South Korea CMERC­HI (South Korea) SEED (Singapore) UK Biobank (UK) 527 (CMERC-HI) 33 (6.3%) of 527 had CVD events during the 5-year follow-up 8,551 (SEED) 310 (3.6%) of 8551 had CVD events 47,679 (UK Biobank) 337 (0.7%) of 47679 had CVD events Age Gender Hypertension Dyslipidaemia Diabetes Smoking status BMI Fasting glucose level Retrospective cohort study Tseng et al [ 17 ] May 2021 Reti-CVD, derived from retinal photographs, indicates a higher CVD risk, and serves as an effective tool for identifying individuals with a ≥ 10% 10-year CVD risk, including those in the borderline-QRISK3 category. It accurately identifies high-risk individuals, with a 10-year risk of 13.1% (CI: 11.7%–14.6%), enhancing early intervention and refining risk assessments, especially for those with a 10-year risk of 7.5%–10%.…”
Section: Main Textmentioning
confidence: 99%
“…Rim et al added the score to PCE-ASCVD to predict SCORE CVD events and Tseng et al added the score to QRISK3 to predict 10-year CVD respectively. 28,29 They both reported small improvements in predictive performance after adding retinal image-derived scores to the models. In another study, Reti-CVD was used to identify people at intermediate and high risk of CVD according to established clinical risk scores (PCE-ASCVD, QRISK3 and Framingham Risk Score), and reported that it could effectively identify these groups.…”
Section: Discussionmentioning
confidence: 99%
“…We found a series of studies on prediction of CAC from one research group, where they developed and validated a retinal fundus image-based score referred to as Reti-CVD or RetiCAC, and its utility was compared to existing CVD risk scores. [28][29][30] The score was proposed as a non-invasive and cost-efficient alternative to the computer tomography-derived CAC score. Multiple validation studies investigated the incremental predictive value of RetiCAC on top of established clinical risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations